Uji validitas LKS berbasis problem solving bermuatan keterampilan 4C pada materi dinamika partikel dan hukum newton tentang gravitasi kelas X SMA/MA - Indah Septia Ningsih; Yenni Darvina; Ramli Ramli; Renol Afrizon (Universitas Negeri Padang, 2020)
21st century skills are needed that emphasize the ability of everyone to be able to think critically in connecting science with the real world, mastering information technology, being able to work together and communicate. So that everyone should have the ability to use media and information technology to be able to answer the demands of the 21st century. In responding to the demands of the 21st century, the government has designed efforts to improve the quality of education in Indonesia by developing the 2013 revised 2017 curriculum. The development of the 2017 revised 2017 curriculum contains important points, including: 1) the strengthening of character education. 2) 4C skills consisting of critical thinking, creativity, collaboration and communication. 3) Higher Order Thinking Skills (HOTS). 4) Literacy. But I focus more on 4C skills. In the reality found in the field is that the teacher has not applied the problem solving learning model in classroom learning activities, the learning activities are still dominated by the lecture method. According to the teacher, many students still depend on the teacher. This can be seen in solving problems in the form of questions in the book. Not only that, the reality on the ground shows that teachers never make non-experiment worksheets. The purpose of this study is to determine the validity of problem solving based LKS based on 4C skills in particle dynamics material and Newton's law of gravity class X SMA / MA. The type of research used is development research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The validation assessment was carried out by 3 physicists by giving a questionnaire instrumentation containing six assessment components, namely the appropriateness of the contents of supporting material, problem solving models, 4C skills, linguistic feasibility, appropriateness of presentation, and the appropriateness of students' worksheets. As for data analysis techniques using descriptive analysis techniques namely the validity test analysis. Based on the results of this study, the validation of student worksheets based on problem solving with 4C skills in particle dynamics material and Newton's law of gravity are 83.6% with a very valid category.